Shape-encoded silica microparticles for multiplexed bioassays1. Issue 60 (4th August 2015) - Kim, Lily Nari; Kim, Mira; Jung, Keumsim; Bae, Hyung Jong; Jang, Jisung; Jung, Yushin; Kim, Jiyun; Kwon, Sunghoon
<x xml:space="preserve">Abstract</x> Shape-encoded silica microparticles for use in multiplexed bioassays were fabricated by using optofluidic maskless lithography (OFML) and tetraethylorthosilicate (TEOS) polymerization.